Fecal Microbiota Transplantation Ameliorates Experimentally Induced Colitis in Mice by Upregulating AhR - Wei, Yan-Ling; Chen, Yu-Qin; Gong, Hao; Li, Ning; Wu, Kang-Qi; Hu, Wang; Wang, Bin; Liu, Kai-Jun; Wen, Liang-Zhi; Xiao, Xiao; Chen, Dong-Feng (Frontiers in Microbiology, 2018)
Ulcerative colitis (UC) is a chronic non-specific inflammatory disease that occurs in the colon and rectum. While fecal microbiota transplantation (FMT) is gaining attention as a clinical treatment of UC, the molecular mechanisms behind this effect have yet to be fully understood. A C57BL/6 mouse model was established to test whether FMT promotes the recovery of colon inflammation. Administration of 2% dextran sulfate sodium (DSS) for 7 days successfully induced acute colitis, as evidenced by diarrhea, hematochezia and colon shortening as well as a decrease in body weight. FMT alleviated the severity of colon mucosa injury and improved histological alterations compared with that of the DSS group. In addition, FMT promoted homeostasis of the intestinal microbiota. Furthermore, FMT upregulated the expression of aryl hydrocarbon receptor (AHR), interleukin-10 (IL-10), and transforming growth factor beta (TGF-β) in colon tissues. These results suggest that the significant anti-inflammatory effect of FMT may be attributed to its promotion of IL-10 and TGF-β production and AHR activation. Based on these results, FMT had a favorable therapeutic effect on DSS-induced colitis.